Short-Term Prognostic Index for Breast Cancer: NPI or Lpi. (28th December 2010) - Van Belle, V.; Decock, J.; Hendrickx, W.; Brouckaert, O.; Pintens, S.; Moerman, P.; Wildiers, H.; Paridaens, R.; Christiaens, M. R.; Van Huffel, S.; Neven, P.
Abstract : Axillary lymph node involvement is an important prognostic factor for breast cancer survival but is confounded by the number of nodes examined. We compare the performance of the log odds prognostic index (Lpi), using a ratio of the positive versus negative lymph nodes, with the Nottingham Prognostic Index (NPI) for short-term breast cancer specific disease free survival. A total of 1818 operable breast cancer patients treated in the University Hospital of Leuven between 2000 and 2005 were included. The performance of the NPI and Lpi were compared on two levels: calibration and discrimination. The latter was evaluated using the concordance index (cindex), the number of patients in the extreme groups, and difference in event rates between these. The NPI had a significant higher cindex, but a significant lower percentage of patients in the extreme risk groups. After updating both indices, no significant differences between NPI and Lpi were noted.